Description of a new species and record of Bactrocera Macquart (Diptera,Tephritidae) from China - Zhou, Li-Bing; Chen, Xiao-Lin; Deng, Yu-Liang; Wang, Shao-Jun (Zootaxa, 2013)
One new species, Bactrocera (Zeugodacus) anala Chen et Zhou, sp.nov, and one newly recorded species, B. (Z.) armillata (Hering, 1938), from China are described and illustrated. The male of B. (Z.) armillata (Hering) was discovered for the first time and as a result the species is moved from subgenus Bactrocera to subgenus Zeugodacus. In addition, the mor-phological differences and comparing illustrations of B. (Z.) adusta (Wang et Zhao) and B. (Z.) biguttata (Bezzi), are pro-vided.